Issues and Challenges of Modernization in Nepal: A Development Perspective (Nepalese Journal of Development and Rural Studies, 2023)
This paper aims to explore the issues and challenges of modernization in development practice in Nepal. The paper is based on the synthesis of secondary sources of information for generating and validating the argumentation. Modernization is indeed an essential aspect of socio-economic progress. Nepal, being a developing country, faces numerous challenges in its pursuit of modernization. This paper discusses the key challenges encountered in the process of modernization, including infrastructural limitations, cultural and social barriers, political instability, and environmental sustainability. By understanding and addressing these challenges, Nepal can effectively navigate its path toward sustainable development and ensure the well-being of its citizens. It therefore concludes with the immediate correction of the mainstream paradigm of modernization making it more micro, small and people-friendly. The paper could contribute to the wider spectrum of development studies in the particular context of Nepal including research scholars, policymakers and development practitioners.